169. Targets for Optimizing Oral Antibiotic Prescriptions for Pediatric Outpatients in Japan. (26th November 2018) - Uda, Kazuhiro; Kinoshita, Noriko; Morisaki, Naho; Okubo, Yusuke; Kasai, Masashi; Horikoshi, Yuho; Miyairi, Isao
Abstract: Background: In Japan, 92% of antibiotics consumed are oral agents most of which are prescribed at outpatient clinics. Universal health insurance and the full reimbursement program for children enables to patients to be treated and obtain prescriptions without any charge in the majority of institutions. Thus, it is possible that unnecessary antibiotic prescription for viral illnesses is common due to free medical access in Japan. As part of a national project to formulate an effective method of antimicrobial stewardship for pediatric outpatients, the aim of our study was to identify key targets for optimizing oral antibiotic use in children by analyzing what factors are related to their prescription in three pilot districts. Methods: We analyzed data on oral antimicrobial prescription patterns for children aged <16 years in three districts (Setagaya ward, Fuchu city, and Kobe city) using national database in Japan. Oral prescriptions were categorized according to their class, spectrum, clinic specialization, and type of clinical setting. The antibiotic spectrum was categorized as narrow, broad, or ultra-broad. Results: In total 13, 869, 332 antibiotic prescriptions were collected for analysis. The proportions of narrow, broad, and ultra-broad spectrum antibiotics were 12.4%, 73.3%, and 14.2%, respectively. The proportions of narrow and ultra-broad spectrum antibiotics were 10.8% and 15.4% in primary care clinics and 23.4% and 5.4% in hospital, respectively. Otolaryngologists prescribed the most antibiotics to children at a rate 1.3 times higher than pediatricians (Figure 1). Dermatologists prescribed 58.7% of all tetracyclines (Figure 2). Three classes of third-generation cephalosporins, quinolones, and penems were prescribed mostly by pediatricians and otolaryngologists. Conclusion: Ultra-broad spectrum antibiotics were prescribed more often in primary care clinics. As the use of specific oral antibiotics differ according to the specialty of each clinic, targeting the clinics specialty and the antibiotic agents used may be key to optimizing oral antibiotic use for pediatric outpatients. Disclosures: All authors: No reported disclosures.